PEMBELAJARAN BERBASIS BLENDED LEARNING DENGAN MODEL INKUIRI TERBIMBING UNTUK MENINGKATKAN HASIL BELAJAR - Risfy Arrifah Rahmah; Siti Nurul Hidayati (Jurusan IPA, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Negeri Surabaya, 2022)
This study proposed to describe the implementation of learning, students’ responses, and learning outcomes in aspects of attitude and knowledge based on blended learning with guided inquiry model. This research used a pre-experimental with one group pretest and posttest design. Subjects in this research were 32 students of VII-D class in SMPN 14 Gresik in the Academic Year 2021/2022. The data were collected using observations, questionnaires, and test in the form of learning implementation observation sheets, student response questionnaires, attitude assessment sheets, and test assessment sheets as instruments. The results showed that the learning process was good to excellent at every stage and the positive responses from students showed excellent categories. Learning outcomes of social attitudes, including cooperative attitudes, responsibility, conscientious attitudes, and discipline attitudes, were declared complete with a good and excellent predicate mode values. The result of N-Gain test analysis acquire in the medium category so that students learning outcomes experienced a significant increase. Based on the description above, it can be concluded that there is an effect of blended learning-based with a guided inquiry model in improving the learning outcomes on science learning of heat and its transfer.